PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI NON AKADEMIK DI SD MUHAMMADIYAH PARAKAN KABUPATEN TEMANGGUNG - Agus Rofi’i; Ngasbun Egar; Ghufron Abdullah (STKIP Subang, 2023)
Education aims to produce quality individuals. This is a mandate for schools to strive to produce outstanding students. The achievements achieved by students in non-academic fields can be obtained by the role of a school principal as a good manager who can organize and manage the school optimally. The role of the Principal as an innovator is also very much needed to come up with brilliant ideas and concepts so that they can spur student achievement in non-academic fields. This research aims to determine the extent of the role of the Principal as a manager and innovator in improving non-academic achievement at SD Muhammadiyah Parakan, Temanggung Regency. This research is a qualitative descriptive study. The research subjects were the principal, teachers, school committee and trainers for extracurricular pencak silat activities. Data collection techniques using observation, interviews and documentation studies. Test the validity of the data using triangulation of sources and techniques. Data analysis uses qualitative analysis, namely through data collection, data condensation, data presentation and drawing conclusions. The principal at SD Muhammadiyah Parakan Temanggung Regency plays a very important role in improving non-academic achievements in pencak silat. Planning begins with preparing the Principal's Work Plan (RKKS), holding a meeting at the start of the school year and creating a program of extracurricular activities together with all school stakeholders. Organizing is done by dividing tasks, providing task descriptions and making a schedule of extracurricular activities. Pencak silat extracurricular activities are carried out by adding to PJOK lessons. Direct evaluation in the field can produce continuously increasing achievements, but school principals have not used a SWOT analysis and are still hampered by the lack of special training facilities. Increasing students' non-academic achievements in non-academic fields, especially pencak silat, is also achieved through innovative physical and mental training and variations in techniques and strategies as well as collaboration with external parties. This really requires full support from various parties, especially from foundations related to providing infrastructure, financing extracurricular activities and accommodation when holding competitions outside of school.